Assessment of shear bond strength of glass ionomer cement reinforced by different amounts of Hydroxyapatite - Hameed, Mohammed R. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: This study was done to assist bond strength of glass ionomer cement reinforced by different amount of HydroxyapatiteMaterials and methods: In this study a hydroxyapatite materials were added to glass ionomer cement at different ratios; 10%, 15%, 20%, 25% and 30% (by weight) and the bond strength was detected by construction a cylinders from these mixed materials, constructed on exposed dentine of human extracted premolar teeth and by Zwick’s universal testing machine the bond strength were detected for these mixed materials.Results: Results showed that the glass ionomer cement reinforced by hydroxyapatite has higher bond strength than conventional glass ionomer cement and the hydroyapatite powder to glass ionomer cement powder ratio by weight best to be 25%.Conclusion: The addition of hydroxyapatite to conventional glass ionomer cement increased its bond strength to dentine.